1994
DOI: 10.1017/s0022112094002016
|View full text |Cite
|
Sign up to set email alerts
|

Active vorticity control in a shear flow using a flapping foil

Abstract: It is shown experimentally that free shear flows can be substantially altered through Subsequently, the experiments are repeated in a different facility at larger scale, resulting in Reynolds number 20000, in order to obtain force and torque measurements. The purpose of the second set of experiments is to assess the impact of flow control on the efficiency of the oscillating foil, and hence investigate the possibility of energy extraction. It is found that the efficiency of the foil depends strongly on the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(159 citation statements)
references
References 17 publications
9
148
0
2
Order By: Relevance
“…In this latter case, the interaction between the foil and vortex can lead to substantially increased or decreased lift, affecting the performance of the foil. This has been demonstrated theoretically by the work of Streitlien [72] and experimentally by Gopalkrishnan [30] where the relative positions were altered via the phase between foil oscillation and vortex shedding. In this case, identifying the relative location of the external vortex to the foil is critically important for predicting the type of affect that will result from the interaction [30].…”
Section: Discussionmentioning
confidence: 85%
“…In this latter case, the interaction between the foil and vortex can lead to substantially increased or decreased lift, affecting the performance of the foil. This has been demonstrated theoretically by the work of Streitlien [72] and experimentally by Gopalkrishnan [30] where the relative positions were altered via the phase between foil oscillation and vortex shedding. In this case, identifying the relative location of the external vortex to the foil is critically important for predicting the type of affect that will result from the interaction [30].…”
Section: Discussionmentioning
confidence: 85%
“…Red is high thrust and blue is low thrust, white represents the value of a single foil. known to consist of two primary vortices of alternating sign shed by the foil per cycle (Gopalkrishnan et al 1994;Anderson et al 1998;Read et al 2003). This wake structure is similar to a drag-producing von Kármán street of a bluff body, although the signs of the vortices on each side of the 'street' is reversed in the flapping foil case because it produces thrust instead of drag.…”
Section: Results From Full Simulationsmentioning
confidence: 93%
“…Gursul & Ho (1992) demonstrated that unsteady motion of airfoils can cause a very high lift coefficient, and work by Anderson et al (1998) shows that oscillating foils are able to produce propulsive thrust very efficiently. Experimental and computational works on the performance of an oscillating lifting surface in the presence of oncoming vorticity (Koochesfahani & Dimotakis 1988;Gopalkrishnan et al 1994;Anderson 1996; reveal that proper phasing between the foil motion and the encounter with oncoming vorticity can yield a significant increase or decrease in efficiency. The principal modes of foil-vortex interaction with a street of alternating-sign vortices can be summarized as (Gopalkrishnan et al 1994): (a) Vorticity annihilation, where foil-generated vorticity interacts destructively with the oncoming vorticity, resulting in the generation of a weak vortex street downstream of the foil.…”
Section: Vorticity Control Mechanismsmentioning
confidence: 99%